Conventional Treatments Cannot Improve Outcomes of Early-Stage Primary Breast Marginal Zone Lymphoma - Liu, Hailing; Zhang, Jing; Quan, Lin; Cao, Lei; Miao, Yi; Zhao, Xiaoli; Shen, Haorui; Wang, Li; Xu, Wei; Li, Jianyong; Fan, Lei (Frontiers in Oncology, 2021)
Introduction Primary breast marginal zone lymphoma (PBMZL) is a rare occurrence, and less is known about its characteristics, treatments, and outcomes. Methods We retrospectively reviewed 370 cases of early-stage PBMZL from the Surveillance, Epidemiology, and End Results database. Statistical analyses were performed to describe clinical features, determine prognostic factors, and compare different therapeutic strategies. Results At a median follow-up of 68.5 months, the 5-year overall survival (OS) and disease-specific survival (DSS) rate was 81.2% and 95.4%, respectively. We divided the cohort into 4 treatment groups and compared their characteristics and survival: radiotherapy (RT)±surgery (Sx) (n=142, 38.4%), Sx alone (n=71, 19.2%), any chemotherapy (CT) (n=63, 17.0%), and none of the above (n=94, 25.4%). Age of onset and laterality of lesions tended to relate to the choice of different treatments. Multivariate Cox analysis showed that advanced age (>60 years), concomitant tumor, and any CT (vs RT±Sx) predicted poorer OS, while for DSS, there was no meaningful indicator (P>0.05). Patients aged >60 years or treated with any CT seemed to have shorter DSS, but the difference only approached statistical significance. Then we applied a propensity score-matched analysis to demonstrate that neither RT- nor Sx-containing therapy could bring a better OS or DSS. The competing risk model suggested that CT was the only contributor to higher PBMZL-specific mortality. Conclusion Our results show an indolent behavior of early-stage PBMZL with long-term survival. Conventional oncological treatments fail to bring survival benefits, especially CT is detrimental to survival, suggesting that observation may be advisable in the management of early-stage PBMZL and further research on novel targeted agents is warranted for patients in need.